Temperature regime of Kateřinská Cave - STŘEDA, Tomáš; STŘEDOVÁ, Hana; VYSOUDIL, Miroslav (Contributions to Geophysics and Geodesy, 2012)
Air and rock surface temperature regime was monitored in Kateřinsk´a Cave in Moravian Karst (Czech Republic, South Moravia). Highly accurate temperature sensors with data logger were used for air temperature measurement. Rock surface temperature was monitored by infrared thermometer and infrared thermal camera. Statistical and graphical processing and 2D map were carried out. The rock surface and air temperature increase as the distance from the entrance increases. The highest dynamics of interior air temperature (amplitude 14.3 °C) and the lowest average temperature (4.03 °C) were detected near the entrance. At a distance of 10 m from the entrance the minimum rock surface temperature was –8.74 °C and maximum 8.60 °C. Rock temperature amplitude decreasesas the distance from the entrance increases (at the distance of 271-280 m reached the minimum value 1.19 °C). The strongest correlation between internal temperature in remote part of the cave and external temperature was found when external data series shifted 22 days backward. Maximum temperatures in remote part are affected by attendance. Maximum daily amplitude (MDA) in remote parts reached up to 0.69 °C while MDA near the entrance (up to 4.27 °C) is caused by external weather.